Step
*
1
of Lemma
compact-product
1. [T] : Type
2. [S] : T ⟶ Type
3. ∀p:T ⟶ 𝔹. ((∃x:T. p x = ff) ∨ (∀x:T. p x = tt))
4. ∀t:T. ∀p:S[t] ⟶ 𝔹.  ((∃x:S[t]. p x = ff) ∨ (∀x:S[t]. p x = tt))
5. p : (t:T × S[t]) ⟶ 𝔹
⊢ (∃x:t:T × S[t]. p x = ff) ∨ (∀x:t:T × S[t]. p x = tt)
BY
{ (RenameVar `d' (-2)
   THEN (InstHyp [⌜λt.isr(d t (λs.(p <t, s>)))⌝] 3⋅ THENA Auto)
   THEN Reduce (-1)
   THEN D -1
   THEN ExRepD) }
1
1. [T] : Type
2. [S] : T ⟶ Type
3. ∀p:T ⟶ 𝔹. ((∃x:T. p x = ff) ∨ (∀x:T. p x = tt))
4. d : ∀t:T. ∀p:S[t] ⟶ 𝔹.  ((∃x:S[t]. p x = ff) ∨ (∀x:S[t]. p x = tt))
5. p : (t:T × S[t]) ⟶ 𝔹
6. x : T
7. isr(d x (λs.(p <x, s>))) = ff
⊢ (∃x:t:T × S[t]. p x = ff) ∨ (∀x:t:T × S[t]. p x = tt)
2
1. [T] : Type
2. [S] : T ⟶ Type
3. ∀p:T ⟶ 𝔹. ((∃x:T. p x = ff) ∨ (∀x:T. p x = tt))
4. d : ∀t:T. ∀p:S[t] ⟶ 𝔹.  ((∃x:S[t]. p x = ff) ∨ (∀x:S[t]. p x = tt))
5. p : (t:T × S[t]) ⟶ 𝔹
6. ∀x:T. isr(d x (λs.(p <x, s>))) = tt
⊢ (∃x:t:T × S[t]. p x = ff) ∨ (∀x:t:T × S[t]. p x = tt)
Latex:
Latex:
1.  [T]  :  Type
2.  [S]  :  T  {}\mrightarrow{}  Type
3.  \mforall{}p:T  {}\mrightarrow{}  \mBbbB{}.  ((\mexists{}x:T.  p  x  =  ff)  \mvee{}  (\mforall{}x:T.  p  x  =  tt))
4.  \mforall{}t:T.  \mforall{}p:S[t]  {}\mrightarrow{}  \mBbbB{}.    ((\mexists{}x:S[t].  p  x  =  ff)  \mvee{}  (\mforall{}x:S[t].  p  x  =  tt))
5.  p  :  (t:T  \mtimes{}  S[t])  {}\mrightarrow{}  \mBbbB{}
\mvdash{}  (\mexists{}x:t:T  \mtimes{}  S[t].  p  x  =  ff)  \mvee{}  (\mforall{}x:t:T  \mtimes{}  S[t].  p  x  =  tt)
By
Latex:
(RenameVar  `d'  (-2)
  THEN  (InstHyp  [\mkleeneopen{}\mlambda{}t.isr(d  t  (\mlambda{}s.(p  <t,  s>)))\mkleeneclose{}]  3\mcdot{}  THENA  Auto)
  THEN  Reduce  (-1)
  THEN  D  -1
  THEN  ExRepD)
Home
Index